INVESTING IN SPEAKING, BECOMING A TEACHER: IDENTITY, IDEOLOGY, AND CAPITAL AMONG PRE-SERVICE ENGLISH TEACHERS - Rudha Widagsa; Dery Tria Agustin; Andi Rahmawan; Pramugara Robby Yana; Nevi Ana Amelia Hapsari (JEELL (Journal of English Education, Linguistics and Literature), 2026)
This study examines how Indonesian pre-service English teachers invest in developing speaking competence and how such investment is mediated by identity, ideology, and capital. Drawing on a qualitative case study of two final-year teacher candidates, data were generated through interviews, observations, and collection of documents, and analyzed using thematic analysis. The findings show that investment is enacted through strategic engagement across formal, informal, and digital learning spaces, rather than through effort alone. Participants' investment is shaped by their emerging identities as future teachers, their negotiation of language ideologies, and their access to and mobilization of diverse forms of capital. The study argues that speaking development is inseparable from processes of professional becoming and social positioning. Highlighting alignment across identity, ideology, and capital, this current study extends the investment in language learning theory. This study also has implications for teacher education practices.